Human Chorionic Plate-Derived Mesenchymal Stem Cells Restore Hepatic Lipid Metabolism in a Rat Model of Bile Duct Ligation - Yun Bin Lee; Jong Ho Choi; Eun Nam Kim; Jin Seok; Hyun-Jung Lee; Jung-Hwan Yoon; Gi Jin Kim (Hindawi Limited, 2017)
In cholestatic liver diseases, impaired bile excretion disrupts lipid homeostasis. We investigated changes of lipid metabolism, including mitochondrial β-oxidation, in a rat model of bile duct ligation (BDL) in which chorionic plate-derived mesenchymal stem cells (CP-MSCs) were transplanted. Serum cholesterol level, which was elevated after BDL, was significantly decreased following CP-MSC transplantation. The expression levels of genes involved in intracellular lipid uptake, including long-chain fatty acyl-CoA synthetases and fatty acid transport proteins, were decreased in rats after BDL; however, they were not significantly changed by subsequent CP-MSC transplantation. Carnitine palmitoyltransferase 1A (CPT1A), a rate-limiting enzyme in mitochondrial β-oxidation, was upregulated after BDL and then was downregulated after CP-MSC transplantation. CPT1A expression was changed via microRNA-33-a posttranscriptional regulator of CPT1A-in a peroxisome proliferator-activated receptor α-independent manner. Cellular adenosine triphosphate production-an indicator of mitochondrial function-was reduced after BDL and was restored by CP-MSC transplantation. Expression levels of heme oxygenases also were significantly affected following BDL and CP-MSC transplantation. Lipid metabolism is altered in response to chronic cholestatic liver injury and can be restored by CP-MSC transplantation. Our study findings support the therapeutic potential of CP-MSCs in cholestatic liver diseases and help in understanding the fundamental mechanisms by which CP-MSCs affect energy metabolism.